Cheetah (Acinonyx jubatus) mortality and survival in fenced reserves as part of a managed metapopulation across South Africa - Schroeder, Michelle M. (Department of Biological Sciences, 2020)
Large carnivores require expansive habitat to meet their life history needs making them vulnerable to the loss and fragmentation of natural habitat. This, in addition to human persecution has led to substantial population and range reductions of most of the world’s large carnivores over the past century. Cheetahs are no exception, occupying only 12% of their historic range in South Africa. Reintroduction programs have attempted to re-establish cheetahs to parts of this historic range, and increasingly the potential exists for their conservation in smaller fenced game reserves. However, this requires managers to maintain demographic and genetic diversity. In 2011, the Endangered Wildlife Trust initiated a project which coordinates movements between reserves using a metapopulation framework. This coordinated management approach is still in its infancy and little data exist on how reintroduction success varies amongst individuals and reserves. This study aims to examine the causes of mortality and the factors influencing cheetah survival on 20 reserves using individual life history records from 1993-2018. We assessed demographic, environmental, and management factors that are predicted to influence cheetah survival using a Cox proportional hazard model. Predation, mostly by lions (Panthera leo) accounted for 39% of known mortalities. However, the presence of spotted hyena (Crucota crucuta) posed the greatest threat to survival. Contrary to my prediction, translocation improved survival when controlling for age. Survival has also improved with time since the coordinated metapopulation approach was initiated in 2011. We created a nomogram which can be used by practitioners to predict cheetah survival within the metapopulation. Our study shows the importance of monitoring reintroduction efforts and encourages similar methods be used for other species of conservation concern that are managed within a metapopulation framework.